Ventricular Septal Defect and Mitral Regurgitation Due to Penetrating Cardiac Trauma; a Case Report and Review of Literature - Mortezaeian , Hojjat; Tabib, Avisa; Pouraliakbar, Hamidreza; Anafje, Mohsen; Ebrahimi, Pouya; Soltani, Parnian (Archives of Academic Emergency Medicine, 2024)
Penetrating cardiac trauma is a fatal condition and can result in the injury of various parts of the heart. Ventricular Septal Defect (VSD) following these traumas occurs only in 1-5% of cases. The patients' conditions depend on location, size, and concomitant injuries. One of the uncommon coincidences with the VSD is Mitral Regurgitation (MR) due to injury to sub-valvular structures. In this study, we report a case of concomitant traumatic-induced VSD and MR in a 14-year-old boy following a stab wound to his chest. The patient was a teenage boy coming to the Rajaei Cardiology Hospital emergency room following a stab wound to the anterior and left part of his chest. Despite primary urgent surgery, his breathlessness had continued for three more months. Evaluations with Transthoracic Echocardiography (TTE) revealed VSD with concomitant MR, but there was no papillary muscle rupture. Cardiac Magnetic Resonance Imaging (MRI) and angiographic evaluation confirmed the provisional diagnosis. The Amplatzer VSD occluder repaired the VSD, and the patient was discharged following the resolution of his symptoms. Although the MR has been present in the follow-up echocardiography, the patient has been asymptomatic. Since the initial presenting symptoms and signs of VSD and MR might be subtle or delayed, imaging modalities such as TTE and Transesophageal Echocardiogram (TEE) are beneficial in determining the diagnosis and the optimal treatment.